2016
DOI: 10.3171/2016.7.gks161494
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for vestibular schwannomas: average 10-year follow-up results focusing on long-term hearing preservation

Abstract: OBJECTIVEThe aim of this study was to reappraise long-term treatment outcomes of stereotactic radiosurgery (SRS) for vestibular schwannomas (VSs). The authors used a database that included patients who underwent SRS with a unique dose-planning technique, i.e., partial tumor coverage designed to avoid excess irradiation of the facial and cochlear nerves, focusing on tumor control and hearing preservation. Clinical factors associated with post-SRS tumor control and long-term hearing preservation were also analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 34 publications
6
58
0
1
Order By: Relevance
“…10,17,18,25,26,33,37,43 Several factors have been suggested to affect hearing preservation, including tumor volume, pretreatment hearing status, age, cochlear dose, brainstem cochlear nucleus dose, and marginal dose ≤ 13 Gy. 8,9,11,21,26,33,38,43,46 Similarly, we found that patients with Grade I hearing fared better regarding hearing preservation. This was clearly evident when we compared these patients with those with Grade II hearing.…”
Section: Radiosurgery For Vs and Hearingsupporting
confidence: 62%
See 2 more Smart Citations
“…10,17,18,25,26,33,37,43 Several factors have been suggested to affect hearing preservation, including tumor volume, pretreatment hearing status, age, cochlear dose, brainstem cochlear nucleus dose, and marginal dose ≤ 13 Gy. 8,9,11,21,26,33,38,43,46 Similarly, we found that patients with Grade I hearing fared better regarding hearing preservation. This was clearly evident when we compared these patients with those with Grade II hearing.…”
Section: Radiosurgery For Vs and Hearingsupporting
confidence: 62%
“…The incidence of CPA meningiomas with serviceable hearing on presentation is reported to be 39%-88%. 23,34,35,46 In the current study the incidence was 27%. The wide incidence variability is probably related to the location criteria, as the CPA location is a wide space located between the lateral cerebellum and pons.…”
Section: Radiosurgery For Cpa Meningiomas and Hearingmentioning
confidence: 40%
See 1 more Smart Citation
“…However, long-term data with reasonably large patient cohorts are missing and few quality-of-life evaluations after SRS for VS have been presented to date [1][2]. Moreover, most published series comprise smaller heterogeneous patient groups treated with inconsistent radiosurgical techniques and doses [3][4][5]. While there has been a tendency to treat increasingly smaller and sometimes asymptomatic tumors, concerns have been raised regarding long-term hearing toxicity and cases of suspected malignant transformation [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Our above-mentioned criteria for neurological death, neurological deterioration, local recurrence, and complications have been widely confirmed based on our previous publications. 14,[31][32][33][34][35][36]38…”
Section: Clinical Outcomesmentioning
confidence: 99%